ONLINE BUSINESS COMPANY MARKETING STRATEGY MARKET SEGMENT GENERATION Z - Muh. Ridwansyah; Sampara Palili; Muhammad Tang (Universitas Kristen Indonesia Toraja, 2022)
The discussion in this journal will focus on how the marketing strategy of online business companies in capturing market share, especially the Generation Z who dominates the world's population today. The digital economy concept is not much different from the general economic concept, but what distinguishes it is the transaction system in carrying out economic activities. The results of the study explain that online motorcycle taxi companies such as Gojek have the power as pioneers of online motorcycle taxi companies in Jakarta, this is a solution for Jakarta residents, especially Gen Z whose population is very dense so that the existence of Gojek will greatly assist Gen Z residents in meeting their needs, especially the costs involved. cheap according to the site www.aturduit.com. Gojek's weakness is a problem that must be resolved by the operator because it is related to the company's internals in this case is the